802 The Predictive Role of Initial Brain Imaging on Seizure Development in Pediatric Traumatic Brain Injury. (April 2023) - Sciscent, Bao Y.; Bailey, David; Chand Daggubati, Lekhaj; Hallan, David; King, Steven; Trifoi, Mara; Rizk, Elias Boulos
Abstract : INTRODUCTION: Pediatric traumatic brain injury (TBI) poses risk for early post-traumatic seizures (EPTS). Antiepileptic drugs are often prescribed prophylactically, though limited evidence exists regarding their effectiveness in pediatric TBI. Neuroimaging has been predictive of EPTS in adult TBI, but this is not well studied in children. Given the heterogeneous nature of TBIs, injury type and location may serve as predictors of seizure development. METHODS: This is a single-center retrospective analysis of 348 pediatric patients with TBI from January 2011 to June 2021 treated with levetiracetam. Factors analyzed include age, sex, GCS, dosage and date of levetiracetam administration, presence of seizures, medical and surgical management, and findings on CT imaging. The primary outcome was the prevalence of seizures within 7 days of injury. RESULTS: On multivariate analysis, the risk of having seizures any time within 7 days of injury was decreased in children with contusions (OR .425 [.205-.880], p = 0.021), simple skull fractures (OR .226 [.079-.648], p = 0.006), and complex skull fractures (OR .370 [.175-.784], p = 0.009). Findings of SDH, traumatic SAH, and pneumocephalus did not significantly increase the risk of EPTS. On univariate analysis of patients who developed seizures after levetiracetam, the only significant imaging factor for EPTS was SDH (OR 4.398 [1.447-13.370], p = 0.009). On multivariate analysis, no imaging characteristics were predictive of EPTS, but older children had a decreased risk of EPTS (1-2 yo OR .095 [.016-.560], p = 0.009; 3-18 yo; OR .006 [0-.132], p = 0.001) despite levetiracetam prophylaxis. CONCLUSIONS: This study demonstrates that regardless of initial neuroimaging, younger age is associated with an increased risk of seizures despite prophylaxis. Further studies are needed to determine the predictive value of imaging characteristics in developing EPTS in pediatric TBI patients.